Bactericidal and Anti-biofilm Activity of the Retinoid Compound CD437 Against Enterococcus faecalis - Tan, Fang; She, Pengfei; Zhou, Linying; Liu, Yiqing; Chen, Lihua; Luo, Zhen; Wu, Yong (Frontiers in Microbiology, 2019)
Enterococcus faecalis (E. faecalis) is a biofilm-forming pathogen that is a main cause of nosocomial infections. In recent years, drug resistance for enterococci has become increasingly severe due to widespread antibiotic abuse. Therefore, novel antibacterial agents are urgently needed. In this study, the synthetic retinoid compound CD437 was found to have a potent bactericidal effect on E. faecalis. In addition, CD437 exhibited synergistic effects when administered in combination with gentamicin and additive effects when combined with ceftriaxone sodium. CD437 also inhibited the biofilm formation of E. faecalis and had a bactericidal effect on the mature biofilm. Moreover, CD437 exhibited antibacterial and biofilm-inhibiting effects against Staphylococcus. No bactericidal action of CD437 was observed against the gram-negative bacillus Pseudomonas aeruginosa PAO1, but PAO1 biofilm extracellular polymeric substances matrix formation was reduced. Taken together, these studies indicate that CD437 has the potential to be developed as a novel antibacterial drug.